Molecular Detection of EMT Markers in Circulating Tumor Cells from Metastatic Non-Small Cell Lung Cancer Patients: Potential Role in Clinical Practice - Annalisa Milano; Francesca Mazzetta; Sabatino Valente; Danilo Ranieri; Laura Leone; Andrea Botticelli; Concetta Elisa Onesti; Salvatore Lauro; Salvatore Raffa; Maria Rosaria Torrisi; Paolo Marchetti (Analytical Cellular Pathology)
Background. Non-small cell lung cancer (NSCLC) is the most common cause of cancer-related mortality; nevertheless, there are few data regarding detection of circulating tumor cells (CTCs) in NSCLC, compared to other kinds of cancers in which their prognostic roles have already been defined. This difference is likely due to detection methods based on the epithelial marker expression which ignore CTCs undergoing epithelial-mesenchymal transition (CTCsEMT). Methods. After optimization of the test with spiking experiments of A549 cells undergoing TGF-β1-induced EMT (A549EMT), the CTCsEMT were enriched by immunomagnetic depletion of leukocytes and then characterized by a RT-PCR assay based on the retrieval of epithelial and EMT-related genes. Blood samples from ten metastatic NSCLC patients before starting treatment and during chemotherapy were used to test this approach by longitudinal monitoring. Ten age- and sex-matched healthy subjects were also enrolled as controls. Results. Recovery experiments of spiked A549EMT cells showed that the RT-PCR assay is a reliable method for detection of CTCsEMT. CTCsEMT were detected in three patients at baseline and in six patients after four cycles of cysplatin-based chemotherapy. Longitudinal monitoring of three patients showed that the CTCsEMT detection is related to poor therapeutic response. Conclusions. The RT-PCR-based approach for the evaluation of CTCsEMT phenotype could be a promising and inexpensive tool to predict the prognosis and the therapeutic response in NSCLC patients.